Heterofunctional nanomaterials: fabrication, properties and applications in nanobiotechnology - Kumar, S. Anil; Khan, Mohammad Islam (Journal of Nanoscience and Nanotechnology, 2010)
Nanotechnology and nanoengineering includes a novel class of materials that are gaining significant recognition to pursuit technological/biological advances in diverse fields including, biology, medicine, electronics, engineering etc. due to their unique size- and shape-dependent intrinsic physicochemical, optoelectronic and biological properties. Characteristics such as high surface to volume ratios and quantum confinement results in materials that are qualitatively different from their bulk counterparts. These properties not only make them suitable for numerous applications in existing and emerging technologies, but also have outstanding role in many fields that provide inspiration for their fabrication. In Today's trend nanotechnology is spreading vigorously where researchers all over the world are focusing towards their synthesis and applications. Therefore, this review is helpful for the researchers in the field of nanobiotechnology/nanomedicine, providing a brief overview of nanotechnology, covering nanomaterial synthesis methods (with emphasis on environmentally benign greener approaches), their properties, and applications; such as drug delivery, bio-labeling, nanotoxicity etc. The influence of synthesis methods and surface coatings/stabilizing agents and their subsequent applications is discussed, and a broad outline on the biomedical applications into which they have been implemented is also presented.
Keywords: Bio-Fabrication; Bio-Labeling; Cell imaging; drug delivery; Greener Synthesis; Nanomaterials; Nanotoxicity